High Plasma Polyamine Levels Are Associated With an Increased Risk of Poststroke Cognitive Impairment: A Multicenter Prospective Study From CATIS - He, Yu; Jia, Yiming; Liu, Yi; Chang, Xinyue; Yang, Pinni; Shi, Mengyao; Guo, Daoxia; Peng, Yanbo; Chen, Jing; Wang, Aili; Xu, Tan; He, Jiang; et al. (Journal of the American Heart Association, 2025)
Polyamines have been suggested to play pivotal roles in ischemic stroke and neurodegenerative disorders, but the associations of plasma polyamines with poststroke cognitive impairment (PSCI) remain unclear. We aimed to prospectively investigate the associations of plasma putrescine, spermidine, and spermine with PSCI among patients with ischemic stroke in a multicenter cohort study. We measured plasma polyamine levels at baseline among 619 patients with ischemic stroke from a preplanned ancillary study of CATIS (China Antihypertensive Trial in Acute Ischemic Stroke). We used the Mini-Mental State Examination and Montreal Cognitive Assessment to evaluate cognitive function at 3-month follow-up after ischemic stroke, and PSCI was defined as Mini-Mental State Examination score <27 or Montreal Cognitive Assessment score <25. According to the Mini-Mental State Examination score, plasma polyamines were positively associated with PSCI. The adjusted odds ratios of PSCI for the highest versus lowest quartile of putrescine, spermidine, and spermine were 1.81 (95% CI, 1.09-3.00), 1.81 (95% CI, 1.09-3.01), and 1.92 (95% CI, 1.15-3.20), respectively. In addition, plasma putrescine (net reclassification improvement, 32.08%; <0.001; integrated discrimination improvement, 1.62%; =0.002), spermidine (net reclassification improvement, 25.29%; =0.002; integrated discrimination improvement, 1.22%; =0.006), and spermine (net reclassification improvement, 16.54%; =0.045; integrated discrimination improvement, 1.36%; =0.004) could significantly improve the risk reclassification of PSCI beyond established risk factors. There were similar significant relationships when PSCI was defined by Montreal Cognitive Assessment score. Higher plasma polyamine levels were associated with increased risk of PSCI among patients with ischemic stroke. Our findings suggest that plasma polyamines should be implicated in the pathophysiologic processes of PSCI and may be the potential intervention targets for PSCI. URL: https://www.clinicaltrials.gov; Unique identifier: NCT01840072.